2010
DOI: 10.1590/s1676-24442010000500011
|View full text |Cite
|
Sign up to set email alerts
|

Investigação da LMP1 do EBV e a coinfeçcão do HPV em lesões genitais de pacientes infectados ou não pelo HIV

Abstract: Introdução: Vários estudos têm demonstrado associação do vírus Epstein-Barr (EBV) com neoplasias malignas, inclusive genitais, em que o papilomavírus humano (HPV) é o principal vírus associado às neoplasias epiteliais benignas e malignas. Objetivo: Investigar a presença do EBV e do HPV em lesões genitais de ambos os sexos, em pacientes soropositivos (grupo A) ou não (grupo B) para o vírus da imunodeficiência humana (HIV). Material e método: Selecionados 126 pacientes e 135 lesões anogenitais, sendo 67 paciente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Our rate of anal STDs are similar to the findings of Sobhani et al 26 , who described an 8% rate of EBV coinfection, a 12% rate of CMV anal infection and a 24% rate of HSV anal infection. However, this study found lower prevalence of EBV (7.7%) and CMV (1.5%) infection compared to the findings of Löwhagen et al 27 and Rodrigues et al 9 , who reported a prevalence of HSV and EBV of over 30%. Because we used RT-PCR as a means of diagnosis, and the method is known to be higher than conventional PCR and the culturing of samples 28 ; therefore, we do not consider our results to be contradictory with previous findings, but as features of our study population.…”
Section: Vol 32contrasting
confidence: 85%
See 2 more Smart Citations
“…Our rate of anal STDs are similar to the findings of Sobhani et al 26 , who described an 8% rate of EBV coinfection, a 12% rate of CMV anal infection and a 24% rate of HSV anal infection. However, this study found lower prevalence of EBV (7.7%) and CMV (1.5%) infection compared to the findings of Löwhagen et al 27 and Rodrigues et al 9 , who reported a prevalence of HSV and EBV of over 30%. Because we used RT-PCR as a means of diagnosis, and the method is known to be higher than conventional PCR and the culturing of samples 28 ; therefore, we do not consider our results to be contradictory with previous findings, but as features of our study population.…”
Section: Vol 32contrasting
confidence: 85%
“…The presence of HSV-EBV coinfection as a risk factor for the development of anal cancer among patients of both sexes coinfected with HPV-HIV has already been described [9][10][11] . In the present study, we report five cases of coinfection with EBV.…”
Section: Vol 32mentioning
confidence: 99%
See 1 more Smart Citation